POLITICAL IDENTITY OF THE IKATAN SARJANA MELAYU INDONESIA LANGKAT REGENCY (ISMI) IN LANGKAT ELECTION YEAR 2018 - Regif, Surya Yudha; Kalembang, Elpius; Ode, Samsul (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2020)
Political identity refers to the political mechanisms of organizing identity, both as a political identity as well as a social identity and also as a resource and political means. The view of scholars is a study that can be used as a basis for society to make political choices. Indonesian-Malay Scholar Association Langkat is a scholar as part of the ethnic Malay with the population of the highest number two ethnic identity in the district of Langkat but the winner of the regional head election of 2018 is derived from the Karo ethnic the third largest population in the area. The design of the research uses a qualitative approach based on the phenomenology and Constructivism paradigm in developing science. Research is done on a natural object that develops as is, researchers do not manipulate and researchers are also not affected by the dynamics of the object. The result shows the strength of the alignments of the Malay ethnic group in Langkat Regency in the election of Langkat Regency which makes it one of the victory factor of the Bupati election and vice regent of Langkat Regency in 2018 but not the main factor of victory.